Overall External Surface Dose Rate Measurement of 131I Package and 99mTc Generator at the National Institute of Nuclear Medicine and Allied Sciences - Begum, Ferdoushi; Quadir, Kamila A; Hossain, Md Nahid; Azim, Md Anwar Ul; Banu, Layla Saroware (Bangladesh Journal of Nuclear Medicine, 2018)
Measuring the external surface dose rate of the radioisotope I-131in order to reduce the radiation hazard during the transportation of this is to perform at National Institute of Nuclear Medicine and Allied Sciences (NINMAS) to the hospitals and clinics is a very basic but important requirement. Measured the external surface dose rate of I-131 after receiving the isotope send to NINMAS in shielded packages by Monrol N.P. Company, Turkey and Radioisotope Production Division (RIPD). The authors also measured the external surface dose rate of Tc-99m generator supplied by RIPD, AERE, Saver, Dhaka, Bangladesh, to check whether the radioisotopes package shielding are within the dose rate limit. From this study, the dose rate was found relatively higher for I-131 transportation by the smaller vehicle than large vehicle, although dose rate in both categories of vehicles are within the permissible limit. The external surface dose rates for Tc-99m generator were also found to be within the permissible limit. Bangladesh J. Nuclear Med. 19(1): 9-14, January 2016